Rituximab Therapy for Primary Membranous Nephropathy in a Chinese Cohort - Gao, Shuang; Cui, Zhao; Wang, Xin; Zhang, Yi-miao; Wang, Fang; Cheng, Xu-yang; Meng, Li-qiang; Zhou, Fu-de; Liu, Gang; Zhao, Ming-hui (Frontiers in Medicine, 2021)
Abstract Background: Rituximab has become one of the first-line therapies for the treatment of moderate and high-risk primary membranous nephropathy (pMN). We retrospectively reviewed 95 patients with pMN who received rituximab therapy and focused on the therapeutic effects and safety of this therapy in a Chinese cohort. Methods: 95 consecutive patients with pMN diagnosed by kidney biopsy received rituximab and were followed up for > 6 months. Four weekly doses of rituximab (375 mg/m2) was adopted as the initial administration. Repeated single infusions were administrated to maintain B cell depletion < 5 cells/mL. Results: 91 patients accomplished rituximab therapy with the total dose of 2.4 (2.0, 3.0) g. 64/78 (82.1%) patients achieved anti-PLA2R antibody depletion in 6.0 (1.0, 12.0) months. 53/91 (58.2%) patients achieved clinical remission in 12.0 (6.0, 24.0) months, including complete remission in 18.7% of patients and partial remission in 39.6% of patients. Multivariate logistic regression analysis showed that severe proteinuria (HR 1.22, P=0.006) and the persistent positivity of anti-PLA2R antibodies (HR 9.00, P=0.002) were independent risk factors to no-remission. The remission rate of rituximab as an initial therapy was higher than rituximab as an alternative therapy (73.1% vs. 52.3%, P=0.038). 45 adverse events occurred in 37 patients, but only one patient withdrew from treatment due to severe pulmonary infection. Conclusion: Rituximab was effective and safe in Chinese patients with pMN, especially as initial therapy.